PENERAPAN TEKNOLOGI TEPAT GUNA PENGELOLAAN LIMBAH BUDI DAYA RUMPUT LAUT DI PANTAI AMAL KOTA TARAKAN - Hasullah Hasullah; Ahmad Hernadi; Muhammad Firdan Nurdin; Amrullah Taqwa (LPPM Universitas Nusa Mandiri, 2026)
The coastal area of Pantai Amal, Tarakan City, Indonesia, faces two major environmental challenges: the accumulation of post-harvest seaweed biomass waste and increasing coastal abrasion caused by climate change, both of which threaten environmental quality and the sustainability of local livelihoods. This Community Service Program aimed to develop an integrated community empowerment model by combining appropriate technology, mangrove rehabilitation, and institutional strengthening to address seaweed waste management and climate change adaptation. The program employed a Participatory Action Research (PAR) approach through four iterative stages: Plan, Act, Observe, and Reflect, actively involving community members in planning, implementation, evaluation, and program improvement. The results demonstrated the successful installation of two appropriate technology units, namely a portable solar dryer and a biomass chopper, followed by technical training for 30 community participants, all of whom were able to operate the equipment independently after the training. In addition, 1,000 Rhizophora mangrove seedlings were planted in erosion-prone coastal areas, while a tourism website and official social media platforms managed by the local Tourism Awareness Group (Pokdarwis) were established to strengthen digital promotion and community participation. The novelty of this program lies in the integration of circular economy-based seaweed waste management, ecosystem-based mangrove rehabilitation, and community institutional empowerment into a single community service model. This integrated approach contributes to strengthening local capacity in sustainable resource management, enhancing coastal resilience, and supporting the development of Pantai Amal as a sustainable community-based tourism destination.